Detection Papers with Chromogenic Chemosensors for Direct Visual Detection and Distinction of Liquid Chemical Warfare Agents - Vladimír Pitschmann; Lukáš Matějovský; Kamila Lunerová; Michal Dymák; Martin Urban; Lukáš Králík (Chemosensors, 2019)
This work provides a summary of our results in the area of the experimental development of detection paper for the detection of liquid phase chemical warfare agents (drops, aerosol), the presence of which is demonstrated by the development of characteristic coloring visible to the naked eye. The basis of the detection paper is a cellulose carrier saturated with the dithienobenzotropone monomer (RM1a)−chromogenic chemosensor sensitive to nerve agents of the G type, blister agent lewisite, or choking agent diphosgene. We achieve a higher coloring brilliance and the limit certain interferences by using this chemosensor in the mix of the o-phenylendiamine-pyronine (PY-OPD). We prove that the addition of the Bromocresol Green pH indicator even enables detection of nerve agents of the V type, or, nitrogen mustards, while keeping a high stability of the detection paper and its functions for other chemical warfare agents. We resolve the resistance against the undesirable influence of water by providing a hydrophobic treatment of the carrier surface.